The development and evaluation of a tublysine-based antibody-drug conjugate with enhanced tumor therapeutic efficacy - Guo, Huihui; Xie, Hongsheng; Huang, Yuanyuan; Jia, Junxiang; Kong, Xiangfei; Yang, Qingliang; Gai, Shun; Li, Wenjun; Bai, Lu; Zhang, Lingli; Chen, Xiaoxiao; Ye, Zhicang; et al. (Frontiers in Pharmacology, 2025)
Antibody-drug conjugates (ADCs) offer targeted cancer therapy by delivering cytotoxic agents directly to tumor cells. However, challenges such as relapse, resistance, and diverse patient needs drive ongoing innovation in ADC development. Exploration of new small-molecule toxins with unique antitumor and toxicity profiles is crucial. Tub114, a novel Tubulysin B analog with a hydrophilic ethylene glycol moiety, has been conjugated to the anti-HER2 antibody DX-CHO9, forming the ADC DX126-262. This study examines the efficacy, pharmacokinetics, and safety profile of DX126-262, with a focus on Tubulysin-associated liver toxicity. In vivo efficacy was assessed using three HER2-positive tumor models, with dose-dependent tumor growth inhibition compared to established treatments. Pharmacokinetic studies were conducted in cynomolgus monkeys across a dosing range (3–30 mg/kg) to compare clearance and stability with Kadcyla and Enhertu. Acute toxicity assays were conducted in mice (75 and 150 mg/kg doses), and repeated-dose toxicity was evaluated over five doses, administered every 3 weeks in rats and cynomolgus monkeys. DX126-262 demonstrated significant and dose-dependent tumor growth inhibition across HER2-positive models, with superior antitumor efficacy compared to Kadcyla and comparable efficacy to Enhertu in vivo studies. In pharmacokinetic studies, DX126-262 exhibited a clearance rate similar to Enhertu and enhanced stability compared to Kadcyla. Acute toxicity assays revealed reduced hepatotoxicity at doses of 75 and 150 mg/kg in mice, with improved tolerance. In repeated-dose toxicity studies, DX126-262 was well tolerated in rats at doses up to 200 mg/kg, with the highest non-severely toxic dose (HNSTD) established at 100 mg/kg. In cynomolgus monkeys, DX126-262 demonstrated superior hepatotoxic tolerability without significant bone marrow suppression, with an HNSTD of 30 mg/kg. DX126-262, incorporating Tub114, a novel Tubulysin B analog, effectively mitigates the inherent hepatotoxicity associated with Tubulysin compounds while maintaining strong antitumor efficacy. These findings suggest that DX126-262 could serve as a safer and more effective option for HER2-targeted cancer therapy, warranting further clinical studies to confirm its therapeutic potential.